ANALISA ASPEK ‘FUN’ DENGAN MENGGUNAKAN TEORI VITRUVIUS dan SIR HENRY WOTTON PADA PRODUK MAINAN - Hady Soedarwanto (Narada : Jurnal Desain dan Seni, 2021)
Fun aspect is the main function of toy product design. On toy products for children this may not be a difficult job because aspects of pleasure can be more easily measured by designers. But on adult targets this is no longer easy because there seems to be something complex with regard to this aspect of pleasure. The fun and use of products experienced by adults is thought to be different from the fun and use of toy products experienced by young children, so in this study will find out about what kind of fun experienced by adults in using their toys and what elements of such toys are considered to bring senility. The study aims to find new forms that are dwarfed by adult toy product users.  To answer this, this research is included in the basic research which goes into TKT level 2, namely with the stages of literature study and initial analysis. This is realized by gaining the experience of adult toy fans with the process of interviewing and observation as a user of the product which is then abstracted using the theory of user experience in order to find a model of how to use the toy and then will be reviewed with theory of fun. The next stage of the toy's product properties will then be reviewed using discussions using Vitruvius Theory and Sir Henry Wotton. The results that will be obtained later are expected to explain the model of fun type in using toy products. This is expected to be a useful basis for the development of design science, especially the design of toy products that is to determine the design process of toy products